2019
DOI: 10.1002/pola.29532
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification for nano‐lignocellulose fiber through vapor‐phase‐assisted surface polymerization

Abstract: This study addresses the inherent issues surrounding surface modification methods of nanofibers and proposes an environmentally friendly and less toxic strategy for the surface modification of hydrophilic nanofiber. From the continuation of our previous work, which discussed the easy production of nanofiber (average size: 127 nm) from oil palm mesocarp fiber (OPMF), in this work, the surface of nanofibers (M‐IL‐OPMF) were modified through vapor‐phase‐assisted surface polymerization (VASP) to improve the affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…It has also been reported that the solubility of cellulose in LiOH-urea aqueous solution is higher than that of NaOH-urea solution [32]. In alkali-urea aqueous solution, after 15 N and 23 Na NMR measurements were clarified, adding urea can effectively improve the stability of the alkali-cellulose complex, owing to the strong interaction between alkali hydroxides and urea, and low temperature can accelerate the breakdown of intermolecular hydrogen bonding among cellulose and, thus, prevent the agglomeration of alkali-urea-cellulose inclusion complexes [33].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has also been reported that the solubility of cellulose in LiOH-urea aqueous solution is higher than that of NaOH-urea solution [32]. In alkali-urea aqueous solution, after 15 N and 23 Na NMR measurements were clarified, adding urea can effectively improve the stability of the alkali-cellulose complex, owing to the strong interaction between alkali hydroxides and urea, and low temperature can accelerate the breakdown of intermolecular hydrogen bonding among cellulose and, thus, prevent the agglomeration of alkali-urea-cellulose inclusion complexes [33].…”
Section: Introductionmentioning
confidence: 96%
“…However, these polymers have limited thermal stability, mechanical strength, and low degradation rate [10][11][12]. In addition to biodegradable polymers, polymer materials filled with lignocellulosic materials as renewable reinforcements have also been studied extensively [13][14][15][16][17]. Despite the significant advantages of lignocellulosic materials as filler, these polymer composites cannot still be considered sustainable materials.…”
Section: Introductionmentioning
confidence: 99%
“…13 The vaporphase reaction takes place on the gas-solid interface, which provides a higher grafting rate when compared to the commonly used liquid process. 14 Cervin et al 4 and Rafieian et al 2 prepared hydrophobic CNF aerogel via chemical vapor deposition (CVD) using hexadecyltrimethoxysilane and octyltrichlorosilane, respectively. And the modified aerogel exhibited excellent hydrophobic and lipophilic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the presence of water could be excluded so the self‐condensation and the hydrolysis reactions of silanes encountered in the liquid phase could significantly be reduced 13 . The vapor‐phase reaction takes place on the gas–solid interface, which provides a higher grafting rate when compared to the commonly used liquid process 14 . Cervin et al 4 and Rafieian et al 2 prepared hydrophobic CNF aerogel via chemical vapor deposition (CVD) using hexadecyltrimethoxysilane and octyltrichlorosilane, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[3] The use of industrial wastes in polymer composites can reduce the consumption of petroleum-based plastics and energy used during the processing of raw materials. In addition, it is possible to enhance mechanical properties through optimization of interface adhesion between matrix and additives, [4,5] and to introduce additional functionality according to the structure and properties of solid wastes. Up to now, various industrial wastes and byproducts have been utilized as fillers in polymer composites.…”
Section: Introductionmentioning
confidence: 99%